Customer-Centric Approach : Strategi Diferensiasi Bsi Kcp Tuban Dalam Pemasaran Pembiayaan Pra Pensiun Di Era Digital - Sifa', Moh Agus; Zainuddin, Moch.; Andriani (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Digital transformation and the dynamics of customer needs demand adaptive and customer-oriented marketing strategies in the Islamic banking industry. This study aims to analyze the customer-centric differentiation strategy implemented by Bank Syariah Indonesia (BSI) KCP Tuban in marketing pre-retirement financing products. With a qualitative approach through interviews and field observations, this study reveals that personalized advisory strategies, hybrid services (offline and online), and the use of digital technology such as the BSI Mobile application and chatbots are key to increasing customer engagement and satisfaction. Innovation through the #SiapPensiunTenang digital campaign and the use of customer data for service personalization also strengthen the competitive position of BSI KCP Tuban. The results of the study show that a customer-centric marketing approach can significantly increase interest in pre-retirement financing products and strengthen customer loyalty in the midst of a competitive digital era. These findings provide theoretical contributions to the development of Islamic marketing literature as well as practical implications for Islamic bank strategies in optimizing the pensioner market segment